FcR expression and function in CD4⁺ T cell biology - Simpson, Scott D. (My University, 1995)
Receptors that bind immunoglobulin (Ig) via the Fc domain are known as Fc receptors (FcR). These receptors are integral transmembrane glycoproteins that are expressed on virtually every haematopoietic cell. FcR mediate a wide range of immunological functions from phagocytosis to cellular activation, however, the function and expression of FcR on CD4⁺ T cells is unknown. Thus, in vivo and in vitro studies were undertaken to investigate FcR expression and function on CD4+ T cells.
Previously it has been demonstrated that CD4⁺ T cells activated with antigen-pulsed macrophages or interleukin 1 (IL-1) generated IgG and IgA binding factors (IgGBF and IgABF). These immunoglobulin binding factors (IgBF) are one component of a soluble macromolecule, known as a contrasuppressor factor (CSF). These CSF act to augment IgG or IgA responses in vivo and in vitro in an isotype-specific manner. Serological and functional data presented here demonstrate that the IgGBF and IgABF are soluble FcϒRII/III and FcαR, respectively. sFcR could functionally substitute for the IgBF and enhanced antibody responses in an isotype-specific manner. Recombinant sFcϒRIII/III, at concentrations of 0.01 to 0.5 ng/mI could augment IgG PFC responses. However, at higher concentrations (10 to 100 ng/ml) it failed to augment IgG PFC responses. Furthermore, the enhancing activity of the IgBF/sFcR was mediated through a subset of T cells that adhered to the lectin Vicia villosa (Vv T cells). In xid mice, which are unable to generate CSF, T cells could generate the IgBF. However, the xid mice lacked circulating regulatory Ig (reg Ig) that is also necessary for the generation of the CSF, resulting in defective CSF.
Since activation of CD4⁺T cells induced the generation of sFcϒRII/III, I investigated FcϒR expression on CD4⁺ T cells utilizing an allogeneic activation system. FACS and PCR data from these studies demonstrated that alloactivation of purified CD4⁺ T cells with CH12.LXB cells induced de novo FcΥRIIBI expression within 24 hours and prior to DNA synthesis. The induction of FcΥRIIBI expression could be blocked by anti-MHC class II mAb, however, direct TCR ligation, even in the presence of IL-2, was not sufficient to induce expression. Moreover, the induction of FcΥRIIBi expression on CD4⁺ T cells was not dependent upon the Ig isotype of the CH12.LX B cells. Alloactivation of CD4⁺ T cells with different isotype-switch variants of the CH12.LX B cell line resulted in significant increases in the number of FcΥRIIB1⁺ CD4⁺ T cells. However, alloactivation with the IgG2b⁺ CH12.LX B cell line induced the largest number of FcΥRIIB1⁺ CD4⁺ T cells. Results from this study indicated that the IgG2b⁺ CH12.LX B cell line secreted a soluble factor(s) that augmented FcΥRIIB1 expression on aIloactivated CD4⁺ T cells. Although, the data suggests that this factor is not soluble IgG2b or IL-1, since both failed to induce FcyRIIBI expression on purified CD4⁺ T cells.
In conclusion, these data indicate that alloactivation of CD4⁺T cells induces de novo mRNA and surface expression of FcΥRIIBI within 24 hours and prior to DNA synthesis. In addition, CD4⁺ T cell FcΥRIIBI expression can be augmented by a soluble factor(s) secreted by the IgG2b⁺ CH12.LX B cells. Furthermore, activation of CD4⁺ T cells also induces the generation of sFcΥRII/III and sFcαR. These sFcR participate in the formation of CSF that enhance antibody responses in vivo and in vitro, in an isotype-specific manner, through the activation of Vv T cells.
Keywords: Medicine and Health Sciences; Medicine and Health Sciences